Tricarboxylic Acid Cycle Enzymes and Morphogenesis in Blastocladiella emersonii - Khouw, Boen Tie (1969)
During exponential growth, ordinary colorless (OC) plants of Blastocladiella emersonii consumed little glucose and produced no lactic acid. Similarly, resistant sporangial (RS) plants did not utilize glucose or produce lactic acid during the first 24 hr of exponential growth. During the next 24 hr of RS development, glucose was consumed with the concomitant production of lactic acid which was then reutilized. Lactic acid gradually accumulated again at maturity. Enzyme studies on cell-free extracts indicated the presence of all tricarboxylic cycle enzymes except α-ketoglutarate dehydrogenase at all stages of development of both RS and OC plants. Included among the enzymes detected were an adenosine monophosphate-stimulated, nicotinamide adenine dinucleotide-isocitric dehydrogenase, and citrate-condensing enzyme. When measured on a per plant basis, tricarboxylic cycle enzyme levels increased during the exponential growth of both kinds of plants. Only after the bicarbonate ceased to have effect on RS plant morphogenesis was there a decrease in the levels of the tricarboxylic cycle enzymes when measured on a per plant basis. Specific activity measurements indicated some differences in the differential rates of synthesis among the enzymes studied previous to 36 hr. Preliminary studies utilizing short periods of (14)C-bicarbonate fixation in young RS plants indicated that during the first 4 min most of the label was located in aspartic acid. These results are discussed in terms of previous results and particularly Cantino's hypothesis concerning the relationship between bicarbonate induction and tricarboxylic-cycle enzymes in the morphogenesis of B. emersonii.